Identifikasi Karakteristik Pengecilan Ukuran dengan Metode Sonikasi dari Formula Insektisida yang Ditambahkan Surfaktan Berbasis Sawit - Eka Nur'azmi Yunira; Ani Suryani; Dadang Dadang; Silvester Tursiloadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
Size reduction of pesticide formulation can improve its performance to pest and disease control in plant. Size reduction methods were high speed agitation, ultrasonic emulsification, high pressure homogenization, microfluidic and membrane emulsification. Homogenizer and sonication methods were most widely used because its high effectivity in size reduction. The purpose of this research was to identify the effect of size reduction on physico chemical properties of the insecticide formulation by adding palm oil surfactant. The method of this research was to make an emulsifiable concentrate (EC) formulation using 15% active ingredient of emamectin benzoate, xylene, cationic surfactant of 1%, nonionic surfactants of 6% with DEA and APG surfactant ratio of 2:3. This formulation was mixed using Homogenizer at a speed of 4000 rpm and sonication with frequencies of 42 kHz at various times of 15, 30 and 45 minutes. The best result of this research was using sonication method for 45 minutes. The best physico-chemical properties were emulsion stability after 2 hours, cream formation after 24 hours emulsion, particle size of 0.70 Î¼m with homogenous dispersion, surface tension of 25.54 dyne/cm, contact angle at 0 minutes of 25.05â° and contact angle after 15 minutes of 0â°.